Nuclear Threats Under International Law Part I: The Legal Framework - Anna Hood; Monique Cormier (Journal for Peace and Nuclear Disarmament, 2024)
The international legal status of threats to use nuclear weapons is uncertain. In this article, we map existing prohibitions against nuclear threats at international law and seek to explain the scope and remit of such laws. To that end, the article explores unilateral negative security assurances; prohibitions on threats to use nuclear weapons in international agreements (including the TPNW, the nuclear weapons free zone treaties and their protocols, and the 1994 Budapest Memorandum); the rules concerning threats in the jus ad bellum regime; and the rules relating to threats in the jus in bello regime. Where there is disagreement about the way these international laws apply to threats to use nuclear weapons, we explain the different views and their significance, and we identify where there are gaps in the existing legal framework. This article is the first in a two-part series on the legality of nuclear threats.